(untitled) (Nepal Journal of Environmental Science, 2022)
Biosurfactants have wide applications in pharmaceutical, agriculture and food industries. The research area of biosurfactants is gaining immense attention. The review mentions here the advantages and various substrates used for biosurfactants production. The pre-treatment of substrates for biosurfactants production is also focused. The production of biosurfactants by solid state fermentation is also described. The renewable substrates, yield and microorganisms used for biosurfactant production are also taken into consideration. The screening methods for biosurfactant are also described. The use of renewable sources for biosurfactant production is specially focused in the review. This will be very eco-friendly, easy and economical. More studies need to BE done on large-scale production of biosurfactants using genetically engineered microorganisms.